Analisis Pengendalian Persediaan Bahan Baku dengan Metode Material Requirement Planning pada Home Industry Pembuatan Tempe Ibu Supri di Desa Jatimalang Pacitan - Dhanar Wahyu Safitri; Sunarso (Teewan Journal Solutions, 2025)
This research explores the potential application of the Material Requirement Planning (MRP) method in optimizing raw material inventory management in [specify type of company]. Through a comparative analysis of Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) techniques, this research aims to identify the most suitable combination of methods in the specific context of the company and make new contributions to the related literature. The data required is an overview of Mrs. Supri's Tempe Home Industry, organizational structure, production process, raw material usage data, raw material inventory data, storage cost data, and order cost data. Data collection techniques with interviews. This study concludes that the raw material inventory control policy currently implemented by Mrs. Supri's Tempe Home Industry has not maximized resource utilization. Simulation using the MRP method shows the potential for significant inventory cost savings, which amounted to Rp 1,230,050. Comparative analysis shows that the implementation of the Lot for Lot and Period Order Quantity methods results in lower total inventory control costs (Rp 202,920) compared to the Economic Order Quantity method (Rp 395,220) in the case of Mrs. Supri's Tempe Home Industry. This indicates the significant potential of the application of Material Requirement Planning in optimizing raw material inventory management in this home industry.